A NOVEL STRAIN OF SHIGELLA SPECIES OUTBREAK IN A RESIDENTIAL SCHOOL IN PEMAGATSHEL, BHUTAN, 2012 - Tsheten Tsheten; Dorji Tshering; Kinley Gyem; Sangay Dorji; Sonam Wangchuk; Tri Hari Irfani; Letho Letho (Public Health of Indonesia)
Background: A cluster of suspected shigellosis was reported from health center in Pemagatshel district to Royal Center for Disease Control on 14th May 2012. The investigation was done to determine the cause and risk factor for the outbreak so that appropriate control and prevention measures can be implemented.